Developing a Framework for Technopreneurial Behavior: The Mediating Role of Technopreneurial Intention and Moderating Role of Attitudes - Nur Atiqah Zakiyyah Ramlee; Hardy Loh Rahim; Nursaadatun Nisak Ahmad (Information Management and Business Review, 2024)
Technopreneurship is a combination of technology and entrepreneurship. Entrepreneurs who are involved in technology-based ventures called technopreneurs employ technology throughout their venture operations and produce technology-based services or products. In the era of globalization, especially post-COVID-19 pandemic, technopreneurship has become more significant as it can drive economic growth. Hence, it is very crucial to further investigate technopreneurship behaviour among university students, as they are the future generation that will lead the development of the country and magnify globalization. Few technopreneurs studies have been conducted previously, however, technopreneurs in the Malaysian context are scarce. Thus, this study proposes to investigate the relationship between subjective norms, perceived behavioural control, and technopreneurs' education towards technopreneurs' behaviour, to ascertain the mediating effect of technopreneurs' intention between subjective norms, perceived behavioural control, and technopreneurs' education towards technopreneurs behaviour, and lastly to determine the moderating effect between attitudes, technopreneurs intention, and technopreneurs behaviour, that is based on the Theory of Planned Behaviour. This study proposed a research method through a survey via questionnaire. In determining the sample size, the software of Raosoft is proposed, and for data analysis, the study has proposed SPSS for data screening and PLS-SEM for the main analysis.